Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.26858/ijole.v3i2.9947
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Vocabulary Depth and Breadth to the TOEFL Reading Subtest in IAIN Kediri

Abstract: TOEFL has been provided as a standardized test to measure the English proficiency of non-native speakers. However, one thing should be considered that TOEFL is still a big challenge for non-native English learners, especially for EFL learners. This is one of the factors, related to how proficient the vocabulary knowledge which students have. Therefore, this study aimed to investigate to what extent the relation between vocabulary knowledge, breadth and depth, and TOEFL test, especially reading subtest session.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…She spent much money and time during her failure (Bonyadi, 2019). It became a challenge for her as Asian student, non-native English speaker to pass the exam (Anam, 2019). It is suggested that students should know their ability, strength and weaknesses in order to easily figure out their failure which would enable them to succeed in their learning process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…She spent much money and time during her failure (Bonyadi, 2019). It became a challenge for her as Asian student, non-native English speaker to pass the exam (Anam, 2019). It is suggested that students should know their ability, strength and weaknesses in order to easily figure out their failure which would enable them to succeed in their learning process.…”
Section: Discussionmentioning
confidence: 99%
“…This work aims to investigate an Indonesian EFL student's perceptions and experiences in repeatedly doing standardized English language proficiency test: TOEIC (Test of English for International Communication) and TOEFL (Test of English as a Foreign Language). This standardized test has a significant role in the academic and professional lives of students (Anam, 2019); it contributes positively to students' language proficiency and their future employment if they have higer and valid score in the test (Hsieh, 2017). This present study interviewed an Indonesian EFL student at a National University in Taiwan running an international program.…”
Section: Introductionmentioning
confidence: 99%
“…In learning languages, vocabulary is the first skill to learn, it can develop other skills, productive or receptive skills. Khoirul (2019) said that among of those skills, vocabulary has the biggest role in language proficiency success; speaking, listening, reading, and writing. it can be concluded that in English learning, the learners need English vocabulary to develop every skill, productive or receptive skill.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it only uses one data collection instrument, such as interviews and questionnaires. Whereas studies on TOEFL must be specific (Anam, 2017;Bakeer & Abu-Naser, 2018;Laborda & Álvarez, 2021;Moradi et al, 2020). In the TOEFL test, each material is very specific (Phillips, 2001); for example, listening material is divided into several skills such as listening to short dialogues, long conversations, and long talks.…”
Section: Introductionmentioning
confidence: 99%